Safety and Efficacy of Sacubitril/Valsartan in Patients With a Failing Systemic Right Ventricle: A Prospective Single-Center Study. (2nd December 2022) - Fusco, Flavia; Scognamiglio, Giancarlo; Merola, Assunta; Iannuzzi, Angela; Palma, Michela; Grimaldi, Nicola; Sarubbi, Berardo
Abstract : Background: Sacubitril/valsartan was demonstrated to reduce hospitalization rate and mortality in patients with heart failure with reduced ejection fraction. Data on the effects of sacubitril/valsartan in patients with a systemic right ventricle are still lacking. Methods: Patients with transposition of the great arteries following Senning/Mustard procedure or congenitally corrected transposition of the great arteries with impaired systemic right ventricle systolic function were prospectively included. Primary end points included sacubitril/valsartan safety and efficacy. Primary efficacy end points were NT-proBNP (N-terminal pro-B-type natriuretic peptide) and systolic function improvement. Secondary end points included New York Heart Association class, 6-minute walking distance, and quality of life change. Results: Fifty patients (38±12 years, 60% male, 35% congenitally corrected transposition of the great arteries) were included and followed for 1 year. No major adverse events occurred. Two (4%) patients ceased treatment due to hypotension and 1 (2%) developed a nephrotic syndrome. The target dose was reached in 20 (42%) patients. NT-proBNP values decreased significantly immediately after treatment initiation, while returned to baseline at 1 year. Echocardiography showed progressive fractional area change increase (29.2±5.8 versus 34.9±5.1%; P <0.001), and right ventricle global longitudinal strain (−13.9 [−15.1, −11.8] versus −15.3 [−17.2, −13.4]%; P <0.001) and free-wall global longitudinal strain (−14.3 [−17.3, −12.3] versus −17.2 [−19.3, −15.8]%; P <0.001) raise, whereas tricuspid regurgitation severity improved only in transposition of the great arteries patients ( P =0.006). Moreover, 3-dimensional echocardiography demonstrated right ventricle volumes reduction (end-diastolic volume: 181±63 versus 156±50 mL; P =0.002; end-systolic volume: 117±48 versus 89±33 mL; P <0.001), and significantly increased systemic right ventricle ejection fraction (35.6±8.1 versus 41.5±7.5%; P <0.001). Clinical improvement was suggested by New York Heart Association class change ( P <0.001), increased 6-minute walking distance (425 [333, 480] versus 500 [443, 560] m; P <0.001) as well as improved quality of life at 1-year follow-up. Beneficial effects were observed irrespective of the underlying anatomy and were more pronounced in those on target dose. Conclusions: Our data showed that sacubitril/valsartan is well tolerated and is associated with systemic right ventricle remodeling and improved systolic function as well as improved clinical status, supporting its use in this complex population.